Effect of High, Medium and Low Grain Proportions on Buffalo Rumen Ecosystem - Agarwal, Payal; Kala, Anju; Kamra, Devki Nandan; Chaudhary, Lal Chandra; Agarwal, Neeta (Indian Journal of Animal Nutrition, 2022)
The aim of this study was to detect the major shifts in fermentation, enzymes activities and microbial communities by feeding diet with high, medium and low grain. Buffaloes were adapted to 3x3 switch over design at 64%, 44% and 23% maize grain in diet fed at 90% of DM intake respectively for 21 days. At the end of each treatment, rumen fluid was collected at 0 h and 4 h after feeding. We performed qPCR based absolute quantification of selected rumen microbes in rumen fluid of buffalo. No significant difference was observed in rumen microbial community and enzymatic activity, however, gas produced (ml/ per gram dry matter) and in vitro digestibity (%) were found significantly lower (P< 0.05) in high grain in comparison with low grain. Ammonia nitrogen and lactic acid were significantly higher in high grain than low grain diet. From above experiment we conclude that there are changes in rumen fermentation due to change in grain proportions, which should be closely monitored during the dietary shifts in ruminants.